2017
DOI: 10.1001/jamapediatrics.2016.4151
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics, Risk Factors, and Outcomes Associated With Neonatal Hemorrhagic Stroke

Abstract: IMPORTANCE Hemorrhage into the brain of term newborns often results in major injury and lifelong disability. The clinical epidemiology of neonatal hemorrhagic stroke (NHS) remains undefined, hindering the development of strategies to improve outcomes.OBJECTIVE To characterize the incidence, types, presentations, associated factors, and outcomes of neonatal hemorrhagic stroke. DESIGN, SETTING, AND PARTICIPANTS Population-based, nested case-control study. The Alberta Perinatal Stroke Project, a provincial regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 36 publications
6
100
3
4
Order By: Relevance
“…Participants were identified through the Alberta Perinatal Stroke Program, a population-based research cohort of over 400 children with MRI-confirmed perinatal stroke from 2010 to 2016. 22 Inclusion criteria were children aged 6 to 18 years with unilateral perinatal stroke and at least one recorded mirror movement score. Stroke type was determined based on MRI criteria by blinded experts using validated criteria.…”
Section: Methods Populationmentioning
confidence: 99%
“…Participants were identified through the Alberta Perinatal Stroke Program, a population-based research cohort of over 400 children with MRI-confirmed perinatal stroke from 2010 to 2016. 22 Inclusion criteria were children aged 6 to 18 years with unilateral perinatal stroke and at least one recorded mirror movement score. Stroke type was determined based on MRI criteria by blinded experts using validated criteria.…”
Section: Methods Populationmentioning
confidence: 99%
“…Perinatal stroke participants were recruited through the Alberta Perinatal Stroke Project (APSP), a population‐based research cohort based at the Alberta Children's Hospital consisting of over 200 children with clinical and imaging confirmed perinatal stroke (Cole et al, ). Inclusion criteria consisted of MRI‐confirmed, unilateral perinatal stroke, symptomatic hemiparetic cerebral palsy, term birth, and were 6–19 years old at the time of imaging.…”
Section: Methodsmentioning
confidence: 99%
“…23 2 Inclusion criteria were: (1) MRI-confirmed ischemic perinatal stroke; (2) no identifiable high-likelihood etiology for stroke, such as congenital heart disease or bacterial meningitis; and (3) informed consent/assent.…”
Section: Methods Populationsmentioning
confidence: 99%